Understanding Adolescents’ Perception of Parenting: A Case Study in Bandung, Indonesia - Djudju Sriwenda; Elih Sudiapermana; Joni Rahmat Pramudia; Gumpanat Bariboon (Journal of Nonformal Education, 2025)
Background: Adolescents, defined by the United Nations as individuals aged 10 to 19 years, are a significant population group, numbering 1.3 billion worldwide. Adolescence is a complex period of transition, characterized by rapid physical, cognitive, and psychosocial growth. These developments affect the way adolescents feel, think, make decisions, and interact with many things. This transition is often described as a period of “storm and stress,” which emphasizes the important role of parents in supporting adolescent’s development. Objective: Exploring adolescents' perception of the parental treatment that adolescents receive. Methods: This study used a survey, involving 120 adolescent respondents in Bandung City, consisting of 40 males and 76 females. Data were collected through questionnaires and analyzed descriptively. Result: The study showed that most of the respondents were 14 years old and lived with their families. Although most adolescents feel closer to their mothers, adolescent girls tend to confide in friends more often than their mothers when facing problems.  The findings also show that parents still tend to compare their children with other children, even with neighboring children. Adolescents expect parents not to compare them with siblings and always support their activities. Conclusion: Adolescents as individuals who grow and develop have needs that must be met by parents. They, by following their developmental patterns, want to be treated as people who have authority, want to be heard, want to be cared for, and want to make parents a place to share Research Contribution: This study provides insight into adolescents' perceptions of parental treatment, which can be the basis for the development of more effective programs and interventions in supporting adolescents’s development